On the role of urban tropical tree collections in carbon allocation: expanding their functions beyond cultural and biodiversity conservation (2024)
ABSTRACT: Trees support key processes in both natural and managed ecosystems. In highly intervened urban environments, trees have been generally associated with benefits such as air quality, microclimate regulation, and biodiversity conservation. University campuses contain diverse and well-managed tree collections that provide local functions such as education, conservation, research, and landscaping. However, little has been discussed about these collections in the general urban setting and how they relate to other urban ecosystem processes, such as carbon cycling. This is particularly evident in tropical regions where no current urban forest carbon sequestration estimations are available. In this work, we present the results of a pilot estimation of the carbon storage function of the university tree collection at the Universidad de Antioquia (Medellín, Colombia) through a bounding calculation that combines tree inventory data and allometric equations. Our results show that, on average, the university tree collection (including palms) sequesters 3.4 Mg C/ha/year (4.2x10 14 -2 Mg C/tree/year). Remarkably, our results are comparable to natural tropical forests, particularly in locations with similar climatic and biophysical conditions. When compared to other urban studies, our estimation ranges between 1.2-20.8 times larger than cities and other urban areas with similar estimations. We present a novel integrative method for estimating carbon storage and sequestration that can be widely applied in information-limited tropical contexts. We discuss how management practices of these urban forests contribute to improving their capacity to store carbon more efficiently and effectively participate in other urban ecosystem processes that derive benefits to society. More generally, our results highlight the role of universities and other similar urban tree collections (i.e. botanical gardens and urban parks) in local and regional ecosystem functions and their potential contribution to global carbon cycling.